“Right to Dry” Laws: Protecting the Environment Over Aesthetic Considerations - McEvoy, Sharlene A. (Journal of Management Policy and Practice, 2020)
This article discusses the development and passage by state legislatures of “right to dry laws” which counter the trend of homeowners associations and condominiums banning the presence of clotheslines because of aesthetics and a concern for property values. Some states have passed laws using the terms “solar energy systems”, “solar energy devices” or “solar collectors” but do not mention the term clotheslines. The problem is that the use of dryers has become so common that most people do not even consider using clotheslines. But dryers use a great amount of energy and produce large quantities of greenhouse gas emissions producing 179 million tons of metric carbon dioxide each year. Also, the use of dryers takes a toll causing more wear and tear and shortening the life of clothes. With the impetus toward the use of natural sources of energy like wind and solar, environmentalists should consider lobbying state legislatures to pass laws overruling restrictive covenants that currently ban clotheslines. In light of the urgent concerns about global warming and energy conservation, aesthetic considerations should recede in importance.